"There is not much help for mothers like me": Parenting Skills for Mothers with Borderline Personality Disorder – a newly developed group training program. Issue 1 (December 2016) - Renneberg, Babette; Rosenbach, Charlotte
Abstract Background Dysfunctional relationships and emotion dysregulation are hallmark features of borderline personality disorder (BPD). Women with BPD are, therefore, particularly challenged when raising a child. A group training program was developed for mothers with BPD to enhance their parenting skills and help them raise their children. The program is based on cognitive-behavioral principles and skills derived from Dialectical Behavior Therapy (DBT). Methods N = 15 mothers with BPD who had young children (aged 0–6 years) participated in a 12-week training program. To estimate the participants' impairment, parental stress and psychological distress were assessed before the training. After the training, participants and trainers were asked to provide feedback regarding the evaluation of and the changes due to the training. Results Participants' self-reported stress related to parenting, as well as psychological distress and depressive symptoms, was high. Participants' acceptance of the program was very good. Especially role plays were rated as useful. Trainers evaluated the program as helpful and reported visible changes in participants' behavior and attitudes towards parenting. Conclusions The results on the acceptance of the training program are promising. Trial registration NCT02935218, Unique Protocol ID: RenRos01 Initial release 80 August 2016, last release 13 October 2016; 'retrospectively registered'